2012
DOI: 10.1109/tpwrd.2012.2198672
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Maintainability Improvement of Substations With Aging Infrastructure

Abstract: The increasing size, aging equipment, and complexity of power systems, coupled with present day financial constraints, have made the use of probabilistic methods and reliability indices a necessity for maintaining continuity and quality of service to customers. Proper maintenance-related decisions should address all of these issues to improve system reliability while meeting limited budget constraints. This paper proposes algorithms that enable system-level reliability assessment with detailed modeling of main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 35 publications
(39 reference statements)
0
18
0
1
Order By: Relevance
“…Furthermore, the rates are supposed to be constant quantities especially be time-invariant, but it is widely believed that aging processes and environmental factors influence utterly on components, systems and the expected performances during the time of operation. Corrective maintenances and rehabilitation actions have the noteworthy impacts on working states of a system [10,35,36].…”
Section: Fuzzy Reliability and The Methodology Selectionmentioning
confidence: 99%
“…Furthermore, the rates are supposed to be constant quantities especially be time-invariant, but it is widely believed that aging processes and environmental factors influence utterly on components, systems and the expected performances during the time of operation. Corrective maintenances and rehabilitation actions have the noteworthy impacts on working states of a system [10,35,36].…”
Section: Fuzzy Reliability and The Methodology Selectionmentioning
confidence: 99%
“…In this paper focus is made on the evaluation of substation maintenance performance based on such a powerful concept. In the literature application of TQM concept for power distribution has been reported [12]. But, in this OEE is calculated based on the Loss Structure.…”
Section: Fig 2 Six Big Lossesmentioning
confidence: 99%
“…Markov model is employed to study the equipment deterioration due to aging and maintenance (major & minor) and minimum cut-set method is used to extend the above studies to substation levels as shown in Fig 5. Hence, Markov models for equipment and minimum cut-set based reliability estimations have been combined for the substation level reliability or availability studies [9]. Substation availability is a very crucial index which is used for the substation maintenance optimization.…”
Section: Substation Level Modelling For Reliability With Aging Equmentioning
confidence: 99%